Melatonin promotes the growth and development of lambs by increasing growth hormone and testosterone, targeting on apoptosis signaling pathway and intestinal microflora - Ma, Wenkui; Wu, Hao; Li, Guangdong; Yan, Laiqing; Wang, Likai; Zhao, Mengmeng; Guan, Shengyu; Xu, Shang; Guo, Xiaokai; Liu, Fenze; Ji, Pengyun; Wusiman, Abulizi; et al. (Frontiers in Endocrinology, 2022)
Melatonin is an indole-like neuroendocrine hormone. A large number of studies have shown that melatonin can improve production performance of ewes, but it is not clear in lambs. In this study, the growth and development of the 2-month-old lambs implanted with melatonin were monitored for 60 days. The results showed that the growth rate of body weight and body skew length of lambs with melatonin treatment were significantly improved compared to the controls. The similar results were also observed in red blood cell count, hematocrit, red blood cell volume distribution width, the levels of growth hormone, androgen, immunoglobulin A, immunoglobulin M and albumin. In addition, the cross sectional area of muscle fibers and adipose cells of lambs with melatonin implantation were also significantly increased compared to the controls (P<0.05). To further explore the potential mechanisms, the muscle and adipose tissue were selected for transcriptome sequencing. KEGG enrichment results showed that melatonin regulated the expression of genes related to apoptotic signaling pathway in muscle and adipocytes. Since the intestinal microbiota are involved in the nutritional balance and animal growth, the 16SrRNA sequencing related to the intestinal microbiota was also performed. The data indicated that the structural differences of fecal microflora mainly occur in the pathways of Cardiovascular disease, Excretory system and Signaling molecules and interaction. In brief, melatonin promotes the growth and development of lambs. The potential mechanisms are involved in increasing the growth hormone and androgen, mediating apoptosis signaling pathway and regulating intestinal microbial flora.